Hydrogels in Brazilian Agriculture - João Luiz Lopes Monteiro Neto; Wellington Farias Araújo; Edvan Alves Chagas; Raphael Henrique da Silva Siqueira; Gabriela Almeida Oliveira; Carlos Abanto Rodriguez (Agro@mbiente On-line)
The rational use of water is essentual as it is a finite resource. Consequerntly, studies of methids that minimize water use water are essential. As a result, agricultural hydrogels have been extensively tested in as a means of promoting agriculture improvements because of their water- and nutriente-retention characteristics. However, even though hydrogels are used in several sectors of Brazilian agriculture, there are still very few studies on their applications, the best methods and the quantities to be used. Consequently, there is a need for research into the applicability of this technology in Brazil, so that future research needs can be identified and appropriate decisions made at the production level. Therefore, the aim of this study was to collate currently available information on the applicability of agricultural hydrogels in Brazilian agriculture. Over the last decade, forestry is the sector in Brazil that has most studied and used hydrogels, but others such as fruit- and coffeegrowing have also been involved. The method of applying the polymer in granules directly mixed-in with growth substrates is the most used in the production of seedlings. However, use of hydrated gel at planting sites has also been explored. While synthetic hydrogels are most commonly used, those made of natural materials have great potential due to the low preparation costs and their in-soil biodegradability. The quantities of hydrogel used vary according to the target species, application method and objective.